Effects of Varying Text Message Length and Driving Speed on the Disruptive Effects of Texting on Driving Simulator Performance: Differential Effects on Eye Glance Measures - Rimzim Taneja; Kawther Alali; Mohammed; Ki-Jana Malone; Brandon Buchanon; Ashley Blanchette; Dung Ho; Doreen Head; Randall Commissaris (Safety)
Eye glance analysis and driving performance during texting while driving: Differential effects of varying driving speed versus text message length. Background and Objective. Texting while driving continues to be a significant public health concern. Eye glances off the roadway are a measure of the visual distraction associated with texting while driving. In the present study, we examined the effects of two ‘real-world’ factors relating to the adverse effects of texting on driving performance and eye glances off the roadway: (1) text message length and (2) driving speed. Methods. Subjects ‘drove’ a fixed-base simulator and read, typed and sent text messages while driving. In study #1, the driving speed was 60 mph and the effects of short (1 word) versus longer (8–10 words) texts were compared. In study #2, the text messages were short only and driving speed was 60 or 80 mph. Driving performance was assessed using the Standard Deviation of Lane Position (SDLP). Video recordings of the drivers’ faces were used to assess eye glances from the road to the phone—and back—during texting. Results. Texting while driving impaired driving performance as measured by SDLP, and both longer text messages and faster drive speeds made driving performance even worse. Analysis of the eye glance data, however, revealed different effects of these two manipulations. Specifically, longer text messages were associated with an increase in the number of eye glances to the phone during a text message episode, an increase in the total time spent with the eyes off the road, and an increase in the single longest eye glance from the road. Moreover, with longer text messages the longest single eye glance away from the road typically occurred at or near the end of the text message episode. In contrast, increasing driving speed to 80 mph did not affect any of these eye glance measures relative to driving at 60 mph. Conclusion and Application. Both text message length and driving speed while texting adversely affect driving performance, but they do so via different mechanisms. These results have implications for how to tailor “don’t text and drive” messaging to better serve the public health.